Parallel Processing System Optimization in High-Performance Computing for Fluid Simulation - Sota Yamamoto; kaito Tanaka; Arnes Yuli Vandika (Yayasan Adra Karima Hubbi, 2024)
The growing complexity of fluid simulations in computational science necessitates the use of high-performance computing (HPC) systems. Efficient processing is critical for handling large datasets and complex algorithms, particularly in fields such as aerospace, meteorology, and biomedical engineering. Existing parallel processing methods often face limitations in scalability and resource utilization. This research aims to optimize parallel processing systems for high-performance computing applications in fluid simulations. The study focuses on enhancing computational efficiency and reducing execution time while maintaining accuracy in simulations. A multi-faceted approach was employed, combining algorithmic improvements with architectural enhancements. The research involved implementing advanced parallelization techniques, such as domain decomposition and load balancing, on a cluster of HPC nodes. Performance metrics were collected to evaluate the impact of these optimizations on simulation speed and resource utilization. The optimized system demonstrated a significant reduction in execution time, achieving up to a 60% improvement compared to baseline performance. Enhanced load balancing techniques resulted in more efficient resource distribution, leading to improved overall system performance. Accuracy of the fluid simulations remained consistent with previous results, validating the effectiveness of the optimizations. The study concludes that optimizing parallel processing systems significantly enhances the efficiency of fluid simulations in HPC environments. The findings provide valuable insights for researchers and practitioners seeking to improve computational performance in complex simulations. Future work should explore further optimizations and the integration of emerging technologies to continue advancing the capabilities of fluid simulation in high-performance computing